Penerapan Manajemen Talenta Di Sekolah Dasar (SD) Kharisma Bangsa - Apan Fauzi; Dwika Yuniarti; Lu’lu’a Farah Adiba; Hasyim Asy’ari (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
The purpose of this study is to describe the application of talent management at SD Kharisma Bangsa. The approach to this research is qualitative. The main method of this research is studies supported by field research. Data is collected through documents, research records, and interviews. The data was taken through several research instruments including documents completeness tables, research notes, and interview guidelines. Data analysis is achieved through content analysis techniques. The results showed that SD Kharisma Bangsa has implemented talent management through training programs to support career paths and employee retention. The training includes; Development Teaching Proficiency (DTP), Future Path, Teacher Motivational Day (TMD), and Out-of-school Training.